Flightlessness in insects enhances diversification and determines assemblage structure across whole communities. Issue 1945 (17th February 2021) - Salces-Castellano, Antonia; Andújar, Carmelo; López, Heriberto; Pérez-Delgado, Antonio J.; Arribas, Paula; Emerson, Brent C.
Abstract : Dispersal limitation has been recurrently suggested to shape both macroecological patterns and microevolutionary processes within invertebrates. However, because of potential interactions among biological, environmental, temporal, and spatial variables, causal links among flight-related traits, diversification and spatial patterns of community assembly remain elusive. Integrating genetic variation within species across whole insect assemblages, within a simplified spatial and environmental framework, can be used to reduce the impact of these potentially confounding variables. Here, we used standardized sampling and mitochondrial DNA sequencing for a whole-community characterization of the beetle fauna inhabiting a singular forested habitat (laurel forest) within an oceanic archipelago setting (Canary Islands). The spatial structure of species assemblages together with species-level genetic diversity was compared at the archipelago and island scales for 104 winged and 110 wingless beetle lineages. We found that wingless beetle lineages have: (i) smaller range sizes at the archipelago scale, (ii) lower representation in younger island communities, (iii) stronger population genetic structure, and (iv) greater spatial structuring of species assemblages between and within islands. Our results reveal that dispersal limitation is a fundamental trait driving diversity patterns at multiple hierarchical levels by promoting spatial diversification and affecting the spatial configuration of entire assemblages at both island and archipelago scales.